Effect of Covid-19 in Management of Lung Cancer Disease: A Review - kumar, Roshan; Saha, Purabi; Nyarko, Richard Owusu; Lokare, Priya; Boateng, Anubhav dubey Edward; Kahwa, Ivan; Owusu Boateng, Paul; Asum, Christian (Asian Journal of Pharmaceutical Research and Development, 2022)
COVID-19 outcomes may be more severe in lung cancer patients. As a COVID-19 pandemic spreads, it's critical to identify which people and malignancies are most susceptible. COVID-19 appears to have the worst results in lung cancer patients. Lung damage or reduced lung capacity can be caused by the disease itself or by cancer treatments such as radiation and surgery. The earlier lung cancer is diagnosed, the better the prognosis. As a result, early detection technology for cancer is in high demand. Early diagnosis in large population screens is closely connected to non-invasiveness and cost-effectiveness. As a result, microelectronic-based sensor technology may be used to construct sensitive biomarker detection systems. Various biosensors have recently recognized cancer-related proteins. Researchers are increasingly interested in testing for volatile metabolites found in the breath. Companion testing for innovative anti-cancer drugs and re-biopsy for new therapeutic uses are helping to speed up the development of lung cancer diagnostic tests. This review covers all current lung cancer diagnostic modalities in depth.